Systematic Literature Review: Parenting Methods in Indonesian Families and Their Implications for Academic Achievement, Character Formation, and Youth Resilience - Masduki Asbari (International Journal of Management and Economic Research (IJOMER), 2026)
This study aims to systematically examine the influence of parenting methods in Indonesian families on children’s academic achievement, character formation, and resilience. Using a Systematic Literature Review (SLR) approach guided by the PRISMA framework, this research synthesizes empirical findings from multidisciplinary databases, incorporating both quantitative and qualitative studies. The analysis is grounded in Baumrind’s parenting typology and supported by ecological and family systems perspectives. The results indicate that authoritative parenting, characterized by warmth, responsiveness, and structured guidance, is consistently associated with better cognitive, emotional, and behavioral outcomes. In contrast, authoritarian and neglectful parenting styles tend to be linked with lower academic performance, weaker moral development, and reduced resilience. The review also suggests that parenting practices may contribute to broader educational challenges and emerging social patterns related to youth adaptability. This study contributes by integrating evidence on parenting and developmental outcomes within the Indonesian context, offering a more comprehensive understanding of family influence on human capital development. The findings highlight the importance of strengthening family-based education and collaboration between families, schools, and communities to support sustainable developmental outcomes.